Moving on: Transitions out of care for young people with learning disabilities in England and Sweden. (8th January 2018) - Roberts, Helen; Ingold, Anne; Liabo, Kristin; Manzotti, Grazia; Reeves, David; Bradby, Hannah
Abstract : Accessible summary: When young people with learning disabilities leave the care system, they can experience many problems. Here we describe some of these problems and what they do (or would like us to do) to improve things. Young people do not always want the same things that professionals or family carers want. We do not spend enough time listening to what young people can tell us. Abstract: Background: Young people with learning disabilities are frequently underrepresented in research accounts. This study describes the experiences of young people moving from the care system. Methods: We scoped the English and Swedish literature for first‐hand accounts and interviewed four young people with learning disabilities leaving the English care system. We combined findings from both sources. Findings: "Grey" and campaigning literature are more likely than academic studies to include the voices of service users, but even then, the voices tend to be those of professional or family carers. Both the literature and interviews demonstrate young peoples' awareness and understanding of the social as well as financial benefits of work. Good foster care could be precarious, and young people in unhappy placements lacked direction. Exploitation around a young person's housing and finances could be problems. There was evidence of "threshold" difficulties in accessing services. Conclusions: Despite an NHS commitment to listening to users in the UK, and similar aspirations in Sweden, our search of the literature identified few studies reporting care leavers' with learning disabilities own words. Our data add to the voices of a group frequently silent or silenced. We found evidence of resilience and hope as well as difficulties and frustrations. The accounts in the literature and our interviews provide data on what it can be like to try to operate "the system." The people we spoke with and those whose accounts we found in the literature were thoughtful and engaging. They provide an important source of knowledge for policy and practice.